M-Poma: Innovative Technology for Boosting Exclusive Breastfeeding Practices - Ramli, Nurlaili; Anita, Anita; Magfirah , Magfirah (South Eastern European Journal of Public Health, 2024)
Background: The Indonesian Health Survey data indicates that exclusive breastfeeding coverage is projected to reach 55.5% in 2023, with Aceh showing a lower rate of 49.9%. In Aceh Besar, the coverage was reported at 55.9% in 2022. Notably, women from low-income backgrounds are less likely to engage in breastfeeding practices by the second day postpartum compared to their higher-income counterparts. To address this disparity, the use of smartphone applications offering educational videos about breastfeeding and infant behavior has emerged as a preferred method, particularly among low-income mothers. Objective: This study aims to develop a mobile application called “POMA” (M-POMA) to enhance exclusive breastfeeding practices among infants in the Kuta Baro District of Aceh Besar. Methodology: A Research and Development (R&D) approach was employed to create the Android-based M-Poma application. The development process spanned two years: the first year focused on application design and functionality, while the second year involved training sessions for 25 midwives and 25 community health cadres. These training sessions were critical for testing the application and gathering user feedback. Results: Based on the first year of research, the M Poma application was developed through a collaborative process, including FGDs and in-depth interviews, to ensure the application meets the needs of the community. Year 2 training was conducted for cadres and midwives to provide their valuable input on the application. The M-Poma application has been developed to support exclusive breastfeeding, which is essential for improving infant health. Feedback from Focus Group Discussions (FGD) highlighted the need for content on exclusive breastfeeding, user profiles, and case examples. Training sessions with midwives and community health cadres confirmed that the application is user-friendly, featuring an attractive interface and clear educational materials. Respondents emphasized the importance of a simple login process, engaging visuals, and easily accessible content. The majority of participants found the application’s features intuitive and appreciated the ease of data management within user profiles. Conclusion: While the M-POMA application has made considerable strides, there are still areas that require revision. We highly value the feedback provided by users and remain dedicated to enhancing the application to ensure it is both appealing and efficient.